2022
DOI: 10.1158/0008-5472.can-21-0501
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of IL1 by Dedifferentiated Melanoma Cells Inhibits JAK1-STAT3–Driven Actomyosin Contractility of Lymph Node Fibroblastic Reticular Cells

Abstract: Fibroblastic reticular cells (FRC) are immunologically specialized myofibroblasts that control the elasticity of the lymph node, in part through their contractile properties. Swelling of tumor-draining lymph nodes is a hallmark of lymphophilic cancers such as cutaneous melanoma. Melanoma displays high intratumoral heterogeneity with the coexistence of melanoma cells with variable differentiation phenotypes from melanocytic to dedifferentiated states. Factors secreted by melanoma cells promote premetastatic lym… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Interestingly, our protein-protein interaction (PPI) analysis did not confirm a direct interaction between GNL3L and STAT3. Subsequent literature review uncovered evidence indicating that JAK1 , IFNAR1 , IFNAR2 , and EML4 can activate the STAT3 signaling pathway, contributing to tumor progression ( 23 - 25 ). Correspondingly, our bioinformatics analysis substantiated a positive correlation between GNL3L expression and that of JAK1 , IFNAR1 , IFNAR2 , and EML4 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our protein-protein interaction (PPI) analysis did not confirm a direct interaction between GNL3L and STAT3. Subsequent literature review uncovered evidence indicating that JAK1 , IFNAR1 , IFNAR2 , and EML4 can activate the STAT3 signaling pathway, contributing to tumor progression ( 23 - 25 ). Correspondingly, our bioinformatics analysis substantiated a positive correlation between GNL3L expression and that of JAK1 , IFNAR1 , IFNAR2 , and EML4 .…”
Section: Discussionmentioning
confidence: 99%
“…Whether SpiB regulates expression of both CD44 and CD9 remains to be addressed. In addition, the subcellular distribution of the transcription factors YAP and TAZ are a direct proxy of mechanical signalling that cells receive 33 and two recent studies identified that the nuclear relocalisation of YAP/TAZ correlates with increased tension while their cytoplasmic localisation correlates with decreased tension and relaxation of the FRC network 30,34 . Our imaging indicates that the FRC network may be relaxed in the T cell zone of LNs and may indicate a lower nuclear/cytoplasmic ratio of YAP/TAZ in WT FRCs compared to their SpiB deficient counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Lactic acid, a metabolite released by cancer cells and found to be enriched in tumor-draining LNs of preclinical melanoma and breast cancer models, was identified to modulate FRC metabolism and mitochondrial function, leading to FRC activation as marked by upregulation of PDPN and Thy1 and downregulation of IL-7, without affecting survival and proliferation of FRCs ( Riedel et al, 2022 ). Furthermore, soluble factors released by dedifferentiated melanomas are found to promote FRC elongation, proliferation, and upregulation of the activation markers PDPN, tenascin C, fibronectin, and IL6 in vitro ( Rovera et al, 2022 ). Among the factors secreted by dedifferentiated melanoma cells, IL1α and IL1β cytokines inhibit the contractility of primary human LN fibroblasts and thereby enhance cancer cell invasiveness in vitro.…”
Section: Frc–immune Cell Interactions In Inflammatory Diseases and Ca...mentioning
confidence: 99%
“…Much less is known about the molecular mechanisms mediating FRC reprograming in tumor-draining LNs or lymphoma-bearing lymphoid tissues. FRC relaxation appears to be driven by impaired JAK1-Stat3 signaling, decreased RhoA-Rho pathway activity, and cytoplasmic translocation of the mechano-receptor YAP1 ( Rovera et al, 2022 ), with TNFR and LTβR signaling contributing to the elongation of FRCs in vitro ( Apollonio et al, 2023 ). Bulk RNA sequencing and histological assessment of high-tumor-burden follicular lymphoma tissues demonstrate a significant correlation between LTB , TGFB1 , and CCL21 expression ( Mourcin et al, 2021 ).…”
Section: Frc–immune Cell Interactions In Inflammatory Diseases and Ca...mentioning
confidence: 99%